2022
DOI: 10.1002/ehf2.14143
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐based differences in referral of heart failure patients to outpatient clinics: a scoping review

Abstract: Background Guidelines recommend that hospitalized patients newly diagnosed with HF be referred to an outpatient HF clinic (HFC) within 2 weeks of discharge. Our study aims were (i) to assess the current literary landscape on the impact of patient sex on HFC referral and outcomes and (ii) to provide a qualitative overview of possible considerations for the impact of sex on referral patterns and HF characteristics including aetiology, symptom severity, investigations undertaken and pharmacologic therapy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…25,26 At a health-system level, female patients are less likely to be referred to cardiologists, are less likely to be referred to HF specialists, and are less likely to receive follow-up visits after the initial consultation, all of which may affect GDMT prescription and uptitration. 27,28 Female patients also have reported that their symptoms were not addressed and reported being told that their symptoms were related to hormonal fluctuations in the Veterans Affairs health system. 29 Poor physician-patient communication may lead to an inadequate understanding of the risks of suboptimally treated HF.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 At a health-system level, female patients are less likely to be referred to cardiologists, are less likely to be referred to HF specialists, and are less likely to receive follow-up visits after the initial consultation, all of which may affect GDMT prescription and uptitration. 27,28 Female patients also have reported that their symptoms were not addressed and reported being told that their symptoms were related to hormonal fluctuations in the Veterans Affairs health system. 29 Poor physician-patient communication may lead to an inadequate understanding of the risks of suboptimally treated HF.…”
Section: Discussionmentioning
confidence: 99%